Efektivitas Diorama Augmented Reality pada Materi Tata Surya untuk Meningkatkan Kemampuan Berpikir Kritis dan Motivasi Belajar Siswa - Anjani, Isfaidah Nur; Raharjo, Tri Joko; Sumartiningsih, Sri (UNDIKMA, 2026)
This study aims to analyze the effectiveness of the use of augmented reality (AR)-based diorama media on solar system material in improving elementary school students’ critical thinking skills and learning motivation. The problem in this study is the low level of students’ critical thinking skills and learning motivation due to learning that is still abstract, less interactive, and unable to visualize concepts concretely. This study employed a quantitative approach with a quasi-experimental design (nonequivalent control group design). The research sample consisted of 60 students, including 30 students in the experimental group and 30 students in the control group. Data collection techniques used a critical thinking skills test and a learning motivation questionnaire that had been tested for validity and reliability. Data analysis was conducted using an independent samples t-test.The results showed that there was a significant difference between the experimental group and the control group in terms of critical thinking skills and learning motivation (p < 0.05). The experimental group showed higher mean scores compared to the control group, indicating that the use of AR-based diorama media had a significant positive effect. These findings indicate the novelty in integrating augmented reality technology with diorama media to visualize abstract concepts more concretely. Therefore, AR-based diorama media can be an innovative, interactive, and contextual learning alternative in improving students’ critical thinking skills and learning motivation in science learning at the elementary school level.